Delayed onset atrioventricular block following transcatheter closure of peri-membranous VSD using Amplatzer duct occluder-II device: Discussion with review of literature. (September 2021) - Ghosh, Sanjiban; Mukherji, Aritra; Pathak, Nihar Lalitkumar; Mazumdar, Jayitri; Chattopadhyay, Amitabha
Abstract: Varying degrees of atrioventricular block are not uncommon following transcatheter closure of perimembranous ventricular septal defects. It is however extremely rare following use of Amplatzer duct occluder-II device. The onset of the atrioventricular block and understanding its underlying mechanism are important for successful management. We hereby report a case of delayed onset high-grade atrioventricular block following closure of a perimembranous ventricular septal defect using a duct occluder-II device where the rhythm reverted to sinus following high dose steroid therapy. Such delayed onset atrioventricular block following use of duct a occluder-II device has not yet been reported in literature. Highlights: Complete heart block is one of the most serious complication following transcatheter closure of ventricular septal defect. Direct damage of conduction pathway, perinodal edema and fibrosis are the possible mechanisms of device induced heart block. Understanding the probable mechanism is important for successful management. Delayed onset heart block following closure of ventricular septal defect using Duct Occlude-II has not been reported.